1998
DOI: 10.1046/j.1365-2761.1998.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Loma salmonae‐associated growth rate suppression in rainbow trout, Oncorhynchus mykiss (Walbaum), occurs during early onset xenoma dissolution as determined by in situ hybridization and immunohistochemistry

Abstract: Experimental infection of rainbow trout, Oncorhynchus mykiss (Walbaum), juveniles with Loma salmonae at a water temperature of 15 °C yielded detectable parasite DNA within the gills by week 2 post‐exposure (PE) and detectable spore‐wall antigen within developing xenomas by week 3 PE, as determined by in situ hybridization and monoclonal antibody (Mab) based immunohistochemistry, respectively. The microsporidian was most commonly located within endothelial cells of lamellar basal channels. Whereas the onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 13 publications
5
43
0
Order By: Relevance
“…data). Beaman (1998) found that rainbow trout initially exposed to L. salmonae at lo\v temperatures (5 or 7°C) or at high temperature (21°C) did not develop xenomas, but were still protected following re-exposure at 15OC.…”
Section: Discussionmentioning
confidence: 94%
“…data). Beaman (1998) found that rainbow trout initially exposed to L. salmonae at lo\v temperatures (5 or 7°C) or at high temperature (21°C) did not develop xenomas, but were still protected following re-exposure at 15OC.…”
Section: Discussionmentioning
confidence: 94%
“…Reported effects of other parasitic infections on fish growth and condition have been mixed. For example, parasitic copepods have been reported to impair growth of Atlantic salmon (Birkeland 1996), whereas suppression of growth in Loma salmonae infected rainbow trout was only temporary (Speare et al 1998). In contrast, increased growth rates have resulted from infection with the tapeworm Schistocephalus solidus in laboratory-reared three-spined stickleback (Arnott et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…All fish were infected with Loma salmonae spores using gastric intubation, as described by Shaw et al (1998) and Speare et al (1998b). Gill tissue from L. salmonae-infected chinook, at Week 7 PE, was examined using sub-gross and standard histological techniques (Speare et al 1998a) to ensure the presence of branchial xenomas (containing spores) before intubation.…”
Section: Methodsmentioning
confidence: 99%